Supramol--a program for structure analysis of intercalates using molecular simulations: the structure of VOPO4*C6H4O2 - Koudelka, Bohdan; Capkova, Pavla (Journal of molecular modeling, 2002)
A method of structure analysis of intercalates has been developed that uses a combination of molecular simulations with powder diffraction. The program Supramol for the determination of intercalated structures uses crystal energy minimization in conjunction with powder diffraction data. The program solves the multiple minima problem in molecular mechanics, generating initial models systematically and searching for the global energy minimum by comparing the experimental and calculated diffraction patterns. The program is compatible with the Cerius2 modeling environment. Two intercalated crystal structures solved by Supramol are presented in the present paper: vanadyl phosphate intercalated with p-benzoquinone and the high temperature phase of vanadyl phosphate intercalated with dioxane. The structure of vanadyl phosphate intercalated with p-benzochinone is tetragonal, space group I4/ m, the unit cell parameters a=6.21 A, b=6.21 A, c=20.18 A and the density is rho=2.30 g x cm(-3), Z=4. The crystal structure of vanadyl phosphate intercalated with dioxane (high temperature phase) is monoclinic, space group C2/ m, unit cell parameters are: a= b=8.94 A, c=8.22 A, alpha=gamma=90 degrees, beta=106.30 degrees, Z=4, density 2.248 g x cm(-3).
Keywords: Software; Computer Simulation; organokovové sloučeniny; software; Models, Molecular; interkalátory; krystalografie rentgenová; počítačová simulace; Vanadium; Crystallography, X-Ray; Organometallic Compounds; molekulární modely; vanad; Intercalating Agents